Recombinant Hepatitis A Virus Antigen: Improved Production and Utility in Diagnostic Immunoassays - LaBrecque, F. D. (American Society for Microbiology, 1998)
Hepatitis A virus (HAV) immunoassays use cell culture-derived HAV antigen to detect HAV-specific antibodies. The current method of production of HAV antigen in tissue culture is time-consuming and expensive. We previously expressed the HAV open reading frame in recombinant vaccinia viruses (rV-ORF). The recombinant HAV polyprotein was accurately processed and was assembled into subviral particles. These particles were bound by HAV-neutralizing antibodies and were able to elicit antibodies which were detected by commercial immunoassays. The present investigation compared the production of HAV antigen by standard tissue culture methods to the production of HAV antigen with the recombinant vaccinia virus system. In addition, HAV and rV-ORF antigens were assessed for their utility in diagnostic immunoassays. Serum or plasma samples from HAV antibody-positive and antibody-negative individuals were evaluated by immunoassay that used either HAV or rV-ORF antigen. All samples (86 of 86) in which HAV antibody was detected by a commercial enzyme-linked immunosorbent assay (ELISA) also tested positive by the recombinant antigen-based immunoassay (VacRIA). Similarly, all samples (50 of 50) that were HAV antibody negative also tested negative by the VacRIA. The lower limit of detection of HAV antibody was similar among immunoassays with either HAV or rV-ORF antigen. Thus, in the population studied, the sensitivity and specificity of the VacRIA were equivalent to those of the commercial ELISA. Since production of recombinant antigen is faster and less expensive than production of traditional HAV antigen, the development of diagnostic HAV antibody tests with recombinant HAV antigen appears warranted.